Efisiensi Pemasaran Bunga Mawar Potong (Rosa hybrid) di Desa Kertawangi - Hardiyanto, Tito; Sujaya, Dedi Herdiansah (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2025)
The problems studied in this research are: (1) marketing channels for cut roses, (2) the costs, margins and profits of marketing cut roses, and (3) marketing efficiency based on the percentage of costs of the total production value. The sampling technique for farmers was carried out using the simple random sampling method, while the sample for marketing institutions was taken using Snowball Sampling. The respondents were 30 farmers, 3 collectors, 2 wholesalers and 5 retailers. The data analysis was carried out descriptively quantitatively. The research results show that: (1) There is one marketing channel for cut roses in Kertawangi Village, Cisarua District, West Bandung Regency namely from farmers to collector Ttraders then to wholesalers then to retailers and finally to consumers; (2) The average marketing margin is IDR 2,000 per stalk with an average marketing cost of IDR 153.33 per stalk so the average marketing profit is IDR 1,846.67 per stalk, and (3) Marketing efficiency for collecting traders is 7.32 percent, for wholesalers is 1.00 percent, and for retailers is 3.09 percent, thus the marketing channel for cut roses is an efficient channel because it has an efficiency value of less than 50 percent, the most efficient marketing of cut roses is with wholesalers because the efficiency value is the smallest, namely 1.00 percent.